2020
DOI: 10.1002/mde.3224
|View full text |Cite
|
Sign up to set email alerts
|

Are health care scams infectious? Empirical evidence on contagion in health care fraud

Abstract: This paper examines the presence of contagion in health care fraud across jurisdictional boundaries. Using state‐level data for the United States, we find evidence of contagion in medical fraud. There are also spillovers from border corruption on medical fraud, but no evidence of spillovers from international borders. In other findings, greater urbanization, greater elderly population, and higher hospital occupancy positively contribute to medical fraud, while nursing employment has a mitigating effect. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…www.dartmouthatlas.org, accessed February 18, 2021. Durable medical equipment fraud in South Florida played a central role in Carl Hiaasen's novel "Bad Monkey" (2013).38 Goel (2020) suggests that these spillover effects may extent even beyond state borders, a result consistent with our evidence from HRRs which often cross state lines.…”
supporting
confidence: 65%
“…www.dartmouthatlas.org, accessed February 18, 2021. Durable medical equipment fraud in South Florida played a central role in Carl Hiaasen's novel "Bad Monkey" (2013).38 Goel (2020) suggests that these spillover effects may extent even beyond state borders, a result consistent with our evidence from HRRs which often cross state lines.…”
supporting
confidence: 65%
“…Shepherd and Button argue that organizational inhibitions for immoral behaviors are due to the construction of differential rationalization interpretation; wherever occupational crimes are normalized, the perception that fraud is ordinary, mundane activities, people are more likely to view them as tolerable practices ( 72 ). A study from the United States found that the prevalence of moral hazard in healthcare fraud has a contagious effect ( 73 ). As Chinese say that the law does not blame the public, which means that when a certain behavior has a certain group or universality, even if the behavior contains some illegal or unreasonable factors, the law is difficult to punish.…”
Section: Discussionmentioning
confidence: 99%
“…), or it may wholly or partially subcontract the supply of passports to a private vendor. On the negative side, government involvement might engender possibilities of fraud (Goel, 2021a , 2021b ). Such fraud could entail both monetary and nonmonetary costs.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…On the negative side, government involvement might engender possibilities of fraud (Goel, 2021a(Goel, , 2021b. Such fraud could entail both monetary and nonmonetary costs.…”
Section: Market For Vpsmentioning
confidence: 99%